TEORI DAN APLIKASI PEMIKIRAN KONTEMPORER DALAM PEMBAHARUAN HUKUM KELUARGA ISLAM - Jefry Tarantang; Jefry Tarantang (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2018)
AbstractThe renewal of Islamic law has always coincided with the development and renewal of thought in the Muslim world with respect to the sacred text and discussing topics more closely related to philosophy or thought. Of the many prominent figures of Islamic law thinking are contemporary Islamic legal thought, such as Fazlur Rahman which offers specific moral and legal ideal terms in the meaning of texts and the early division of Islamic tradition, Muhammad Shahrur offers theoretical limits in the provisions of Islamic law, and Abdullah Ahmad An-Na'im who offers an alternative answer based on the theory of nasakh in melalukan reformulation of Islamic law that arises because the theories or results of traditional Islamic legal thinking is no longer relevant to the circumstances of the times. So the offer of renewal of contemporary Islamic legal methods such as Fazlur Rahman, Muhammad Shahrur, and Abdullah Ahmad An-Na'im. Contemporary thinking is applied in the Islamic law reformation method which can be used as a renewal in Islamic family law such as Rahman's double motion theory, Shahrur's boundary theory, and nasakh theory as an alternative answer by Na'im in the context of renewal of family law in accordance with the objectives of Islamic law applies in every place and time (shalih likulli zaman wal makan).Keywords: theory and application, contemporary, renewal, Islamic family law